THE DIAGNOSIS AND TREATMENT OF PANDAS SYNDROME: A CASE REPORT - V. I. Kharitonov; Yu. M. Vinnik; G. I. Selyukov (Русский журнал детской неврологии, 2015)
This paper describes a case of PANDAS in a 12-year-old girl. The unusual clinical manifestations and course of the disease as long-term sneezing attacks make the diagnosis of the syndrome difficult. Long-term video-assisted electroencephalographic monitoring, brain magnetic resonance imaging, and blood biochemical tests could define the nature of the condition. Antibiotic therapy and intravenous immunoglobulin could achieve remission. Further investigations are needed to evaluate the efficacy of antibiotics and intravenous immunoglobulin in this syndrome.